Bilateral traumatic anterior crystalline lens dislocation by watersplash during Songkran festival: Case report - Paradee Kunavisarut (2018)
Objective: To report a case of bilateral anterior dislocated crystalline lens from water splash during the Songkran festival. Material and Method: A healthy 46-year-old woman with a previous history of having water thrown to her face at the Songkran festival complained of acute bilateral painful visual loss. On examination, visual acuity was 0.1 OD, 0.2 OS, and both eyes revealed anterior dislocated crystalline lens with blood in anterior chamber. Her intraocular pressure (IOP) was 8 mmHg OD and 47 mmHg OS. She was initially treated with medication for controlling IOP and inflammation. Eventually, she underwent pars plana vitrectomy, pars plana lensectomy, and scleral-fixated intraocular lens (SF-IOL) in both eyes. Results: The dislocated lens was successfully removed and visual acuity was 0.7 OD and 0.9 OS at 9 months follow-up. Conclusion: Water splash can be associated with anterior lens dislocation and secondary glaucoma. Awareness, careful examination, and prompt referral to an ophthalmologist can prevent complications and preserve the patient's vision.